2020
DOI: 10.2478/raon-2020-0033
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the primary efficacy of microwave ablation of malignant liver tumors by using a robotic navigation system

Abstract: BackgroundThe aim of the study was to assess the primary efficacy of robot-assisted microwave ablation and compare it to manually guided microwave ablation for percutaneous ablation of liver malignancies.Patients and methodsWe performed a retrospective single center evaluation of microwave ablations of 368 liver tumors in 192 patients (36 female, 156 male, mean age 63 years). One hundred and nineteen ablations were performed between 08/2011 and 03/2014 with manual guidance, whereas 249 ablations were performed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 30 publications
(46 reference statements)
0
16
0
Order By: Relevance
“…All of the 34 included works were single-centre studies, of which 26 were retrospective studies (29,30,(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)31,(49)(50)(51)(52)(53)(54)(32)(33)(34)(35)(36)(37)(38), 3 prospective case series(55-57), 3 prospective cohort studies(58-60) and 2 randomised controlled trials (61,62). Two studies reported results using a laparoscopic treatment access (44,55), the other 32 reporting on thermal ablations using a percutaneous approach.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All of the 34 included works were single-centre studies, of which 26 were retrospective studies (29,30,(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)31,(49)(50)(51)(52)(53)(54)(32)(33)(34)(35)(36)(37)(38), 3 prospective case series(55-57), 3 prospective cohort studies(58-60) and 2 randomised controlled trials (61,62). Two studies reported results using a laparoscopic treatment access (44,55), the other 32 reporting on thermal ablations using a percutaneous approach.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies reported results using a laparoscopic treatment access (44,55), the other 32 reporting on thermal ablations using a percutaneous approach. Six studies applied robotic targeting using mechanical tracking (31,47,48,51,60,62), 7 an electromagnetic (EM)-tracked dynamic technique (35,42,50,55,57,59,61) and the other 21 an optically tracked stereotactic aiming device. Baseline study, patient and lesion characteristics, applied ablation and navigation techniques and reported outcomes of the included works are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations